(untitled) (Clinics, 2020)
OBJECTIVE: Fine-needle aspiration cytology is the risk stratification tool for thyroid nodules, and ultrasound elastography is not routinely used for the differential diagnosis of thyroid cancer. The current study aimed to compare the diagnostic parameters of ultrasound elastography and fine-needle aspiration cytology, using surgical pathology as the reference standard. METHODS: In total, 205 patients with abnormal thyroid function test results underwent ultrasound-guided fine-needle aspiration cytology on the basis of the American College of Radiology Thyroid Imaging-Reporting and Data System classification and strain ultrasound elastography according to the ASTERIA criteria. Histopathological examination of the surgical specimens was performed according to the 2017 World Health Organization classification system. Moreover, a beneficial score analysis for each modality was conducted. RESULTS: Of 265 nodules, 212 measured X1 cm. The strain index value increased from benign to malignant nodules, and the presence of autoimmune thyroid diseases did not affect the results (p40.05 for all categories). The sensitivities of histopathological examination, ultrasound elastography, and fine-needle aspiration cytology for detection of nodules measuring X1 cm were 1, 1, and 0.97, respectively. The working area for detecting nodule(s) in a single image was similar between strain ultrasound elastography and fine-needle aspiration cytology for highly and moderately suspicious nodules. However, for mildly suspicious, unsuspicious, and benign nodules, the working area for detecting nodule(s) in a single image was higher in strain ultrasound elastography than in fine-needle aspiration cytology. CONCLUSION: Strain ultrasound elastography for highly and moderately suspicious nodules facilitated the detection of mildly suspicious, unsuspicious, and benign nodules.